Shrink - Prescribing Resiliency Solutions for Streaming - Chandramouli, Badrish; Goldstein, Jonathan (International Conference on Very Large Databases (PVLDB Vol. 10, Issue. 5), 2017)
Streaming query deployments make up a vital part of cloud oriented applications. They vary widely in their data, logic, and statefulness, and are typically executed in multi-tenant distributed environments with varying uptime SLAs. In order to achieve these SLAs, one of a number of proposed resiliency strategies is employed to protect against failure. This paper has introduced the first, comprehensive, cloud friendly comparison between different resiliency techniques for streaming queries. In this paper, we introduce models which capture the costs associated with different resiliency strategies, and through a series of experiments which implement and validate these models, show that (1) there is no single resiliency strategy which efficiently handles most streaming scenarios; (2) the optimization space is too complex for a person to employ a “rules of thumb” approach; and (3) there exists a clear generalization of periodic checkpointing that is worth considering in many cases. Finally, the models presented in this paper can be adapted to fit a wide variety of resiliency strategies, and likely have important consequences for cloud services beyond those that are obviously streaming.